Solve for x in

      

Solve for x in
4x + 2y = x - 3y + 1 = 2x + y + 13.

  

Answers


John
Equate any two equations to get

one equation.

4x + 2y = x - 3y + 1

3x + 5y = 1 ..........(i)

x - 3y + 1 = 2x + y + 13

-x - 4y = 12 ...... (ii)

Solve equations (i) and (ii) i.e

Multiply eqn (ii) by -3

3x + 5y = 1
3x + 12y = -36

-7y = 37;

y = - 377

From (ii) x + 4(-377)

From (ii) x = 4(-377) = -12

x - 1487 = -12

x = 647
johnmulu answered the question on June 8, 2017 at 08:49


Next: What is the difference between valley glaciers and ice sheets?
Previous: How is a pyramidal peak formed?

View More Mathematics Questions and Answers | Return to Questions Index


Exams With Marking Schemes

Related Questions